KEMAMPUAN MENYIMAK MITE SISWA KELAS X SMA NEGERI 1 SUNGAI RUMBAI DENGAN MENGGUNAKAN MEDIA AUDIO - Hastuti, Novia; Mana, Lira Hayu Afdetis; Andheska, harry (Pendidikan Bahasa Indonesia, 2014)
This research has the background of the problems. The first is the pengajaran menyimak only gave in theory ratherthan practice. The second is students had lack consentration in pay attention of teaching material that had been done by a teacher. The third is the books of pembelajaran menyimak were still less to support in teaching and learning process. The fourth is kemampuan menyimak mite of students was not optimal. The fifth is students were more act playfully rather than pay attention. Â The sixth is students were more prefer dreaming than pay attention on learning material that had been given by teacher. The seventh is students were preferred popular story rather than old story. The eighth is there was not any media that is used, the teacher explained about theory only. The purpose of this research is to describe kemampuan menyimak mite siswa kelas X SMA Negeri 1 Sungai Rumbai by using audio based on thema, characteristics, background, plot and finding the interesting things about charachteristic of story.This research is quantitative research by describtive design. The population of this research is the garde of X SMA Negeri 1 Sungai Rumbai, the amount is 192 in six classes. The taken of sample uses proportional random sampling tehnic so that the sample has taken be 36 students. the data analysis is done by doing several steps: (1) give scors in the result of test, (2) turn scors become marks, (3) make a group of the scors toward the result of test, (4) determine avarege, (5) make the histogram based on students skill whole, (6) analyze and discuss the result, (7) conclude the result of finding.The result of research is data per indicator is as following. (1) indicator 1 indicator 1 (thema) classify Hampir Cukup (HC) by avarege 49,99, (2) indicator 2 (charachteristich) classify Lebih dari Cukup (LdC) by avarege 71,76, (3) indicator 3 (backgound) classify Hampir Cukup (HC) by avarege 49,53, (4) indicator 4 (plot) classify Baik (B) by avarege 93,52, (5) indicator 5 (the charachteristic intersting things of mite story) classify Kurang (K) by avarege 42,13. This result that can be gotten, it canbe concluded studentsâ KemampuanÂ  menyimak mite on garde of X SMA Negeri 1 Sungai Rumbai by using audio media is classified Cukup (C) by avarege 62,13 genaraly.